UJI NILAI KEKESATAN PERMUKAAN JALAN BERDASARKAN JENIS PADA LAPISAN PERMUKAAN PADA PERKERASAN LENTUR - Putri, Karolina Ginting; Akhmadali, -; Sulandari, Eti (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
One of the main requirements of paved road layers is the comfortable feeling that the road should be flat. Surface roughness, the slope of the surface and light reflection are the functional requirements of the surface pavement layer. Road surface entanglement is closely related to safety and comfortable feeling of road users. In Pontianak, nearly all roads use flexible pavements. Flexible pavement has some types of surface layers that have different roughness. Therefore, this research wanted to see the relationship between the type of surface layers on flexible pavement with the value of surface roughness. In this research, the value of surface roughness using BPT (British Pendulum Tester). The location of the research was Jalan Nirbaya, Jalan Padat Karya, Jalan Untung Surapati, Jalan Merdeka, Jalan HOS Cokroaminoto and Jalan Urip. The result of the survey showed that latasir has a greater axial value than HRS/WC, and also the temperature also has influence to the value of surface roughness Keyword: Friction Resistance, British Pendulum Tester, British Pendulum Number